Indications and Outcomes for Arthroscopic Hip Labral Reconstruction With Autografts: A Systematic Review - Bessa, Felipe S.; Williams, Brady T.; Polce, Evan M.; Neto, Mansueto; Garcia, Flávio L.; Leporace, Gustavo; Metsavaht, Leonardo; Chahla, Jorge (Frontiers in Surgery, 2020)
Background: The acetabular labrum plays a major role in hip function and stability. The gold standard treatment for labral tears is labral repair, but in cases where tissue is not amenable to repair, reconstruction has been demonstrated to provide superior outcomes compared to debridement. Many types of grafts have been used for reconstruction with good to excellent outcomes. Autograft options include iliotibial band (ITB), semitendinosus, and indirect head of the rectus femoris tendon, while allografts have included fascia lata and gracilis tendon allografts. Questions/Purposes: As allografts are not always readily available and have some inherent disadvantages, the aims of this systematic review were to assess (1) indications for labral reconstruction and (2) summarize outcomes, complications, and reoperation rates after arthroscopic labral reconstruction with autografts. Methods: A systematic review of the literature was performed using six databases (PubMed, CINAHL, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Scopus, and Google Scholar) to identify studies reporting outcomes for arthroscopic labral reconstruction utilizing autografts, with a minimum follow-up of 1 year. Study design, patient demographics, autograft choice, complications, donor site morbidity, reoperation rates, conversion to arthroplasty, and patient reported outcomes were extracted and reported. Results: Seven studies were identified for inclusion with a total of 402 patients (173 females, age range 16–72, follow-up range 12–120 months). The most commonly reported functional outcome score was the modified Harris Hip Score (mHHS), which was reported in six of seven studies. Preoperative mHHS ranged from 56 to 67.3 and improved postoperatively to a range of 81.4–97.8. Conversion to total hip arthroplasty and reoperation rates ranged from 0 to 13.2% and 0 to 11%, respectively. The most common indication for labral reconstruction was an irreparable labrum. Autografts utilized included ITB, hamstring tendons, indirect head of rectus femoris, and capsular tissue. Conclusions: Arthroscopic autograft reconstruction of the acetabular labrum results in significant improvement in the short- and mid-term patient reported outcomes, for properly selected patients presenting with pain and functional limitation in the hip due to an irreparable labral injury.